A Conceptual Review of Emergent State Measurement: Current Problems, Future Solutions. (December 2014) - Coultas, Chris W.; Driskell, Tripp; Burke, C. Shawn; Salas, Eduardo
Team research increasingly incorporates emergent states as an integral mediator between team inputs and outcomes. In conjunction with this, we have witnessed a proliferation and fragmentation of measurement techniques associated with emergent states. This inconsistency in measurement presents a problem for scientists and practitioners alike. For the scientist, it becomes difficult to better understand the nature and effects of various emergent states on team processes and outcomes. For the practitioner, it complicates the process of measurement development, selection, and implementation. To address these issues, we review the literature on emergent states focusing on various measurement strategies, to better unpack best practices. In so doing, we highlight existing research that suggests innovative solutions to the conceptual, methodological, and logistical problems that consistently plague emergent state research. Our aim is to enhance emergent state theory by applying psychometric principles to the measurement techniques associated with them.